GESTATION OF HIGH RISK AND LOW WEIGHT AT BIRTH IN GOIÂNIA - Dayane Cristina Silva Vinhas; Leilinéia Pereira Ramos de Rezende; Cleusa Alves Martins (Universidade Federal de Goias, 2003)
It happened a study of the Specific Hypertensive of Gestation Disease (SHGD) and Low Weight ofNew Born (LWNB) with the objectives to verify the incidence of LWNB in mothers with SHGD and to present someepidemic data. The data was collected through a trial. From January-1998 through December-2002 in a publichospital of Goiânia, we researched 239 files of pregnant women with DHEG and their respective new born. Weverified that 69,70% of the mothers had children with smaller weight than 2500g, leading us to conclude that DHEGinfluences in the incidence of RNBP, because in less than 50% of the cases, there was a birth of pre-term. Most ofthe mothers were pregnant for the first time. More than 50% of them made prenatal, however, only 39,70%accomplished more than six consultations. In 82,85% of the cases, the childbirth was via cesarean operation.